1999
DOI: 10.1002/j.0022-0337.1999.63.5.tb03287.x
|View full text |Cite
|
Sign up to set email alerts
|

Student productivity under requirement and comprehensive care systems

Abstract: This retrospective study reviews the educational and patient care effects of changing from a numerical requirements‐driven clinical curriculum to aa comprehensive care model driven by patient needs and led by faculty group leaders. In September 1994, the Columbia University School of Dental and Oral Surgery implemented a program in which all patient care shifted to a patient care completion model. Core assumptions included creating an educational setting where students were assigned to groups with continuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…Educators have expressed concern that students may put their own needs ahead of the patients as a result (34). Those working without requirements having been shown to be less stressed and equally as productive (35)(36)(37)(38)(39)(40). Holmes et al suggest that students may even be more productive in the absence of requirements (41).…”
Section: 'In Other Dental Hospitals…the Patients Are Too Advanced Formentioning
confidence: 99%
“…Educators have expressed concern that students may put their own needs ahead of the patients as a result (34). Those working without requirements having been shown to be less stressed and equally as productive (35)(36)(37)(38)(39)(40). Holmes et al suggest that students may even be more productive in the absence of requirements (41).…”
Section: 'In Other Dental Hospitals…the Patients Are Too Advanced Formentioning
confidence: 99%
“…Studies have been undertaken previously to describe the effect of the removal of the minimum requirement on student productivity (3, 4) and competence (5, 6). These investigations were all undertaken over 1 year, generally with one group of students required to undertake a minimum number of acts, and one group taking part in a ‘comprehensive care’ programme.…”
Section: Discussionmentioning
confidence: 99%
“…These investigations were all undertaken over 1 year, generally with one group of students required to undertake a minimum number of acts, and one group taking part in a ‘comprehensive care’ programme. In three of these studies, the performance of the students was found to improve in the comprehensive care group (3–5). In particular it has been shown that the students were more likely to complete full treatment plans drawn up at the beginning of the year and in addition, undertook an equivalent number of acts to their colleagues in the minimum requirement group (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations